Clinical protocols for the application of dexamethasone in endodontic therapy: an integrative review (Research, Society and Development, 2022)
The present study aims to analyze, by means of an integrative review, clinical protocols for the application of Dexamethasone to endodontic therapy reported in the scientific literature. To compose this review, national and international articles were included. The main online journal databases PubMed, Lilacs, and SciELO were searched using the following keywords/free terms: "Dexamethasone", "Endodontics", and "Preoperative", with the aid of the Boolean operator "AND". The inclusion criteria were articles in English, Portuguese and Spanish and clinical trials published in the last 10 years, while the exclusion criteria were articles that did not fulfill the information in the title, abstract, articles with years not between 2011 and 2021 and any other article that was not a clinical trial. The results showed that 10 studies presented in the present review showed in their results a significant efficacy of dexamethasone when applied to endodontic therapy. Thus, it is concluded that the painful symptomatology experienced by patients after endodontic therapy can be relieved with dexamethasone for up to 24 hours, which is the period in which most patients report experiencing pain.